Effects of induced alkalosis and caffeine supplementation on 2000 m rowing performance - Carr, A.; Gore, C.; Dawson, B. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Short-term, high intensity exercise performance can be enhanced with caffeine supplementation (Jackman et al., 1996) and sodium bicarbonate ingestion (Carr et al., 2011). Both agents may therefore improve performance in 2000 m rowing events, which require 6-8 min efforts at a high percentage of VO2max (Hagerman et al., 1978). The purpose of this study was to determine the effect of ingested caffeine, sodium bicarbonate, and their combination on 2000 m performance (mean power, Watts), as well as on induced alkalosis (blood and urine pH and blood bicarbonate concentration [HCO3-]), blood lactate concentration ([La-]), gastrointestinal symptoms, and rating of perceived exertion (RPE). Methods In a double-blind, crossover study, 8 well-trained rowers performed 2 x 2000 m rowing-ergometer baseline tests and 4 x 2000 m rowing-ergometer tests after ingesting 6 mg/kg caffeine, 0.3 g/kg body mass (BM) sodium bicarbonate, both supplements combined, or placebo. Capillary blood samples were collected pre-ingestion, pre-test, and post-test. Pairwise comparisons were made between protocols, and differences were interpreted in relation to the likelihood of exceeding the smallest-worthwhile-change thresholds for each variable. A likelihood of >75% was considered a substantial change (Hopkins et al., 2009). Results Caffeine elicited a substantial improvement in 2000 m mean power, with mean (± SD) values of 354 ± 67 Watts vs. placebo with 346 ± 61 Watts; but not for caffeine + bicarbonate combined (352 ± 63 Watts). Pre-test [HCO3-] reached 29.2 ± 2.9 mmol/L with caffeine + bicarbonate and 29.1 ± 1.9 mmol/L with bicarbonate supplementation. There were substantial increases in pre-test [HCO3-] and pH, as well as post-test urine pH after bicarbonate and caffeine + bicarbonate compared with placebo. All subjects reported side effects after ingesting bicarbonate. Discussion The major finding was an improvement of ~2% in 2000 m rowing performance with 6 mg/kg BM caffeine supplementation, consistent with previously reported enhancements for competitive rowers (Bruce et al., 2000). However, when caffeine is combined with sodium bicarbonate, gastrointestinal symptoms may prevent performance enhancement.